The Effect of Water-Soluble Alpinia Galanga Extract on Sleep and the Activation of the GABAAergic/Serotonergic Pathway in Mice - Şahin, Kazım; Korkusuz, Ahmet Kayhan; Sahin, Emre; Orhan, Cemal; Er, Besir; Morde, Abhijeet; Kilic, Ertugrul (Mdpi, 2024)
Background/Objectives: With increasing interest in plant-based compounds that can enhance sleep quality without the side effects of caffeine, Alpinia galanga (AG) has emerged as a promising herbal supplement for improving mental alertness. This study assessed the impact of water-soluble AG extract on sleep quality; the activity of GABAergic, glutamatergic, and serotonergic receptors; and concentrations of dopamine and serotonin in the brains of mice. Methods: The study employed two experimental models using BALB/c mice to examine the impact of pentobarbital-induced sleep and caffeine-induced insomnia. In the first model, a set of 20 mice was assigned to four groups to assess the effects of pentobarbital (42 mg/kg) or pentobarbital with AG extract on sleep induction, with observations made 45 min post-administration. In the second model, 20 mice were divided into four groups to evaluate the impact of caffeine (25 mg/kg) alone or caffeine with varying doses of AG extract (61.25 or 205.50 mg/kg administered orally) on brain activity along with additional analyses on receptor proteins and neurotransmitters. Results: A higher dose of AG extract (205.50 mg/kg) significantly increased total deep sleep duration compared to the caffeine group (p < 0.0001). Furthermore, this dose extended sleep latency and suppressed GABAergic and glutamatergic receptor activity compared to the lower AG dose (p < 0.05). Additionally, the 205.50 mg/kg dose elevated serotonin and dopamine levels compared to caffeine (p < 0.0001), suggesting improved sleep quality alongside enhanced wakefulness. Conclusions: Our data indicate that a higher dose of AG extract improved sleep latency and duration by regulating GABAergic and glutamatergic receptors through the GABAergic/serotonergic pathway in mice.
Keywords: caffeine; GABAergic; sleep quality; neurotransmitters; Alpinia galanga